Unoprostone Activation of BK (K(Ca)1.1) Channel Splice Variants() - Yu, Ling (Biochim Biophys Acta, 2015)
This investigation was conducted to study the relationship between intracellular Ca(2+) and activation of large conductance Ca(2+)-activated K(+) (BK) currents by unoprostone, the first synthetic docosanoid. We used HEK293 cells stably transfected with two BK channel splice variants, one sensitive to unoprostone and the other insensitive. We examined the effects of unoprostone on channel activity in excised inside-out patches and cell-attached patches. The half-maximal stimulation of the sensitive BK channels by Ca(2+) was shifted from 3.4 ± 0.017 nM to 0.81 ± .0058 nM in the presence of 10 nM unoprostone. There was no effect on insensitive channels even at unoprostone concentrations as high as 1000 nM. There was no effect of unoprostone on the voltage dependence of the BK channels. Changes in open probability and effects of Ca(2+) and unoprostone were best described by a synergistic binding model. These data would suggest that Ca(2+) and unoprostone were binding to sites close to one another on the channel protein and that unoprostone binding causes the affinity of the calcium binding site to increase. This idea is consistent with three dimensional models of the Ca(2+) binding site and a putative unoprostone binding domain. Our results have important implications for the clinical use of unoprostone to activate BK channels. Channel activation will be limited if intracellular Ca(2+) is not elevated.